2017
DOI: 10.18632/oncotarget.18682
|View full text |Cite
|
Sign up to set email alerts
|

Additional N-glycosylation mutation in the major hydrophilic region of hepatitis B virus S gene is a risk indicator for hepatocellular carcinoma occurrence in patients with coexistence of HBsAg/anti-HBs

Abstract: The study aimed to determine the association of additional N-glycosylation mutations in the major hydrophilic region (MHR) of hepatitis B virus (HBV) S gene with hepatocellular carcinoma (HCC) occurrence in HBsAg/anti-HBs coexistent patients. A total of 288 HBsAg/anti-HBs coexistent patients and 490 single HBsAg-positive patients were enrolled, including 193 with HCC, 433 with chronic hepatitis B (CHB), and 152 with acute-on-chronic liver failure (ACLF). The HBV S genes were amplified from serum and sequenced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Interestingly, these mutations are significantly more frequent in HBsAg/anti-HBsAg antibodies-coexisting patients who develop HCC than in those who do not. Moreover, they are often detected several years before HCC onset, raising the question of a direct involvement of N-linked glycans in disease progression [ 70 ].…”
Section: Hbv N-glycosylation and The Carcinogenic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these mutations are significantly more frequent in HBsAg/anti-HBsAg antibodies-coexisting patients who develop HCC than in those who do not. Moreover, they are often detected several years before HCC onset, raising the question of a direct involvement of N-linked glycans in disease progression [ 70 ].…”
Section: Hbv N-glycosylation and The Carcinogenic Potentialmentioning
confidence: 99%
“…Functional analysis of the newly discovered mutations was further performed in transfected HepG2 cells. However, neither cell proliferation nor migration was affected in cells expressing HBV-S with additional N-linked glycans [ 70 ].…”
Section: Hbv N-glycosylation and The Carcinogenic Potentialmentioning
confidence: 99%
“…Instead, host cellular immunity and humoral immunity against HBV should be the main reason causing liver damage. It has been reported that the HBsAg produced by some HBV mutants may help virus particles escaping immune surveillance, thus hindering the body’s immune system killing HBV, leading to persistent infection of HBV and continuous liver injury, and finally resulting in the development of liver cirrhosis or even HCC [ 9 , 10 ]. Additionally, HBsAg protein can interfere with some important signaling pathways in hepatocyte, which may induce malignant proliferation of hepatocytes and lead to the occurrence of hepatocellular carcinoma [ 4 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…HBV contains 4 overlapping open reading frames (ORFs) encoding the polymerase (P), core (C), surface antigen (S), and X proteins[ 29 ]. The S gene region is one of the most important open reading frames of the HBV genome, encoding a protein forming an important part of HbsAg[ 30 , 31 ]. Thus, the S gene is not only closely associated with virus replication, transcription, assembly, and secretion processes, but also with cellular and humoral immune responses induced by the virus.…”
Section: Discussionmentioning
confidence: 99%